A performer's exploration of aspects of selected nineteenth-century solo piano works by female composers: Schumann, Chaminade and Beach - Brennan, Deirbhile (Royal Irish Academy of Music, 2024)
Much has been written about the performance of nineteenth-century solo piano music which forms part of the so-called canon of more frequently performed or, what might be considered ‘standard’, repertoire. Many highly regarded, well-known pianists have performed and recorded such works and there are multiple editions including urtext editions of many of these compositions. Contemporary pianists therefore have a wealth of reference resources available to them in the context of informing and preparing their own individual performances. Compositions which are not included in the teaching canon may pose greater challenges. Works by nineteenth-century female composers, for instance, typically do not form part of the canon and the resources available to potential performers of this music are much more limited. Performances and recordings by the most well-known and highly regarded pianists are rare and there may be few reliable editions available. German pianist/composer Clara Schumann (1819-1896), French pianist/composer, Cécile Chaminade (1857-1944), and American pianist/composer, Amy Beach (1867-1944) were each constrained by social mores of the day and, unlike their male peers, did not benefit from formal conservatory training in composition yet all three were prolific in their musical outputs. A key substantial solo piano concert work by each composer is explored from a performer’s perspective with the aim of informing future performances of these works: Clara Schumann’s Variations on a Theme by Robert Schumann, Op. 20, Chaminade’s Sonata in C minor, Op. 21 and Beach’s Ballad, Op. 6. The current scholarship in relation to these works is considered but the thesis focuses on performance considerations including analysis of the works, incorporating references to original manuscripts where available, and performances thereof by myself and others.
Keywords: Music; Piano music; Female composers; Performance; Piano music - 19th century; Schumann, Clara, 1819-1896. Variations on a theme by Robert Schumann, piano, op 20; Chaminade, Cécile, 1857-1944. Sonata, piano, op 21, C minor; Beach, Amy, 1867-1944. Ballad, piano, op 6